Pelaksanaan Evaluasi Formatif Mata Pelajaran Ekonomi Pada Kelas XI di Madrasah Aliyah Al-Badar Kasongan - Endang Sri Suyati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
The approach used is a qualitative approach. To obtain the relevant data is used several methods: 1) interview or interviews, 2) observation, and 3) documentation. The implementation process of data analysis in this research since the beginning of data collection and worked intensively after leaving the field. The data were analyzed by the researchers as soon as possible so that the data obtained are not raw or expired. Analysis of the data include: 1) data reduction, 2) display data, and 3) displays a conclusion and verification. The conclusion of this study are: 1) planning is the preparation of teachers of economics before the formative evaluation, which is to create a syllabus and lesson plans, so that the implementation of the formative evaluation can be run properly, 2) the implementation of the formative evaluation of economic subjects held in Madrasah Aliyah Al-Badr was appropriate the planning of the teacher concerned, 3) follow up the results of the formative evaluation, after carrying out formative evaluation test results will be communicated to students that study results can either continue to the next lesson, but for students who study results have not yet reached KKM will take remedial for repairs the results, 4) the obstacles in the learning process faced by teachers is mastery of the material, because the teachers of economics should be ready in the mastery of the material that will be presented to the learner, 5) the efforts of teachers of economics in the implementation of formative evaluation planning with good.